2011
DOI: 10.1136/bmj.d6462
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise referral schemes in primary care on physical activity and improving health outcomes: systematic review and meta-analysis

Abstract: Objective To assess the impact of exercise referral schemes on physical activity and health outcomes.Design Systematic review and meta-analysis.Data sources Medline, Embase, PsycINFO, Cochrane Library, ISI Web of Science, SPORTDiscus, and ongoing trial registries up to October 2009. We also checked study references.Study selection Design: randomised controlled trials or non-randomised controlled (cluster or individual) studies published in peer review journals. Population: sedentary individuals with or without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
238
5
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(259 citation statements)
references
References 27 publications
11
238
5
5
Order By: Relevance
“…874 A meta-analysis of 8 RCTs showed that exercise referral schemes that provide a clear referral by primary care professionals to third-party professionals to increase exercise or physical activity can increase the number of participants who achieve 90 to 150 min/wk of moderate physical activity and reduce depressive symptoms in sedentary individuals with or without a medical diagnosis (obesity, hypertension, depression, diabetes mellitus). 875 In a qualitative study, stroke survivors described great physical and psychological well-being after participation in an exercise referral scheme. 794,877 There is substantial evidence that rehabilitation services, particularly exercise-based programs, provided in the community after discharge from acute or institutional care can improve cardiovascular health and decrease the risk of cardiovascular events, leading to increased short-term survival rates for individuals who have experienced a stroke.…”
Section: Referral To Community Resourcesmentioning
confidence: 99%
“…874 A meta-analysis of 8 RCTs showed that exercise referral schemes that provide a clear referral by primary care professionals to third-party professionals to increase exercise or physical activity can increase the number of participants who achieve 90 to 150 min/wk of moderate physical activity and reduce depressive symptoms in sedentary individuals with or without a medical diagnosis (obesity, hypertension, depression, diabetes mellitus). 875 In a qualitative study, stroke survivors described great physical and psychological well-being after participation in an exercise referral scheme. 794,877 There is substantial evidence that rehabilitation services, particularly exercise-based programs, provided in the community after discharge from acute or institutional care can improve cardiovascular health and decrease the risk of cardiovascular events, leading to increased short-term survival rates for individuals who have experienced a stroke.…”
Section: Referral To Community Resourcesmentioning
confidence: 99%
“…These patients showed decreases in perceived health status throughout the 12 month data collection period and a continued reliance on medication at the same or a higher rate. Our findings are in contrast to other views that suggest ERS are no better than standard care [11], were ineffective at promoting physical activity in the long-term (over 12 weeks) [12] or only have a marginal effect on increasing physical activity levels [14].…”
Section: Discussioncontrasting
confidence: 56%
“…In our analysis of 12 seriously ill patients participating in an ERS, we found that long-term engagement with a practice-based scheme aided physical activity adherence and increased combined (walking and exercise classes) physical activity levels, in the long-term. These findings are in contrast to recent reviews that found limited evidence to support the use of ERS in primary care [11,14]. The patients in this study were able to give examples of how the physical activity that they had undertaken had positively affected their diagnosed medical conditions over the 12 month period.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations